Selection for barriers between honey bees and a devastating parasite. Issue 12 (17th July 2019) - Evans, Jay D.
Abstract : Rivaling pesticides and a dearth of flowers, the parasitic mite Varroa destructor presents a tremendous threat to western honey bees, Apis mellifera . A longstanding, but minor, pest for the Asian honey bee Apis cerana, these obligate bee parasites feast on developing and adult A. mellifera across several continents. Varroa reproduction is limited to a short window when developing bee pupae are concealed in wax cells. Mated females target developing bees just before pupation and then have about one day to initiate reproduction, eventually laying one male and up to several female offspring. Female mites often fail to reproduce at all, instead waiting in cells until their bee host finishes development and then hitching dangerous rides on a succession of adult bees for up to several weeks, before scouting for a new host pupa. In this issue of Molecular Ecology, Conlon et al. (2019) have explored mite reproductive success via a clever and thought‐provoking association study. In so doing, they have identified a protein whose actions could be integral to the dance between bees and their mite parasites.